Problem of gender culture in contemporary academic discourse - Tokova, Natalia; Maslova, Yuliia; Zukow, Walery (Journal of Education, Health and Sport, 2018)
In article the issues of gender culture in contemporary academic discourse, the notion "gender culture", its constituents and types.